EFEKTIVITAS KEBIJAKAN DESA SIAGA AKTIF DALAM MEMBANGUN COMMUNITY-BASED DISASTER MANAGEMENT (Studi di Desa Karangtinoto Kecamatan Rengel Kabupaten Tuban) - Iswanto, Denny (Jendela Inovasi Daerah, 2024)
One of the strategies for dealing with health problems is the Desa siaga Program. Desa siaga is a village whose population has the resources and ability to prevent and overcome health problems, disasters, and health emergencies with independently. The effectiveness of health services is important in providing good services for the community. This study aims to determine the effectiveness of the Desa siaga Program in Karangtinoto Village Community Health Services and to determine the supporting and inhibiting factors in the implementation of the active Desa siaga Program in Karangtinoto Village. The results of the study have shown that the active Desa siaga has been running well in health services in Karangtinoto Village. This can be seen from the clarity of goals and objectives, the socialization of the program, the availability of adequate infrastructure, and the existence of internal and external supervision in its implementation. The inhibiting factors of this program are limited funds for developing the Desa siaga Program and the absence of cooperation with other parties in the success of the program. For this reason, the suggestions that researchers give are to increase the budget for the Desa siaga, need to build partnerships/cooperation with third parties, and need to provide training to Desa siaga’s officers.